FDS simulations and modelling efforts of travelling fires in a large elongated compartment. (17th November 2020) - Anderson, Johan; Sjöström, Johan; Temple, Alastair; Charlier, Marion; Dai, Xu; Welch, Stephen; Rush, David
Summary: The present paper investigates a travelling fire scenario in an elongated structure (Length 18 m × width 6 m × height 3 m) with a controlled fire source of six trays filled with diesel (width 4 m × length 0.5 m). The fire spread is controlled manually by initiating fires consecutively in the pools. Fire dynamics simulator (FDS) is used to a‐priori investigate variations in geometry, material data and fire load, whereas simulations using the final design and measured heat release rates (HRR) were performed after the test. The input to the model beside fire source and geometry are thermal material data. The FDS simulations were used to determine the appropriate size of the downstands (2 m from the ceiling in the final design) on the side to create a sufficiently one‐dimensional fire spread. The post‐test simulations indicate that although there are a lot of variations not included in the model similar results were obtained as in the test.